The other hidden hand: Soviet and Cuban intelligence in Allende's Chile. Issue 3 (16th April 2018) - Gustafson, Kristian; Andrew, Christopher
Abstract: The role of Soviet and Cuban covert activities in Allende's Chile has not been given sufficient consideration. This paper outlines the significant actions that the KGB and the Cuban DGI undertook there, showing that both organizations played important roles in both operating directly against the CIA and by supporting local actors. The results of their efforts, however, may have been negative to Allende's coalition by focusing on factional or ideological interests. A broad array of sources is brought together to shed light on this historical gap. The result is a new paradigm in which we can consider this dramatic period.